(MOLECULAR MODELING BASED ON AB INITIO METHOD FOR ANTI CORROSION COMPOUND PHENYL-PHYRAZOLINDOLE DERIVATIVES) - Hamdiani, Saprini; Hadisaputra, Saprizal (Jurnal Lembaga Penelitian Universitas Mataram, 2014)
A molecular modeling has been carried out on the phenyl-phyrazolindole derivatives as anti-corrosion by ab initio methods at the HF/DZV level of theory. Quantum-chemical parameters for anti-corrosion compounds such as orbital energies (EHOMO and ELUMO), ionization potential (I), electron affinity (A) and electronegativity (Ï) has a linear relationship with the anti-corrosion efficiency (IE%). The substituent changes on the anti-corrosion compound causes the enhancement of anti-corrosion eficiency. The 1NH2-PI compound has the highest anti-corrosion efficiency of 83.12%. This value is better than the phenyl- phyrazolindole (PI) which has anti-corrosion efficiency of 79.30%. This theoretical study will have a major contribution in helping the design and synthesis of novel anti-corrosion compound that has a higher efficiency